2015
DOI: 10.1097/mnm.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of gastric emptying in obese patients before and after laparoscopic sleeve gastrectomy using radionuclide scintigraphy

Abstract: Radionuclide scintigraphy provides a standard physiologic evaluation of gastric emptying (GE) after laparoscopic sleeve gastrectomy (LSG). This operation can be associated with motor gastric dysfunction and abnormal GE. The aim of this study was to evaluate the short-term effect of LSG on GE quantitative indices for liquids and solids compared with preoperative results. Forty obese patients were divided into two equal groups, the liquid and solid groups. Tc-sulfur colloid GE scintigraphy was performed on all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…However, RYGB was associated with more severe hypoglycemic episodes and RYGB patients had an overall larger number of reactive hypoglycemic episodes than SG. This fact was explained by the postprandial hyperinsulinemia observed after RYGB, inappropriately high despite glucose levels, and not by gastric empting, described to be equally accelerated after both RYGB and SG [52]. A study comparing matched controls to RYGB surgical patients with and without symptomatic hypoglycemia, shown that glucagon-like peptide 1 (GLP-1) had effect on insulin secretion only in RYGB patients, both symptomatic and asymptomatic.…”
Section: Hypoglycemia and Dumping Syndromementioning
confidence: 99%
“…However, RYGB was associated with more severe hypoglycemic episodes and RYGB patients had an overall larger number of reactive hypoglycemic episodes than SG. This fact was explained by the postprandial hyperinsulinemia observed after RYGB, inappropriately high despite glucose levels, and not by gastric empting, described to be equally accelerated after both RYGB and SG [52]. A study comparing matched controls to RYGB surgical patients with and without symptomatic hypoglycemia, shown that glucagon-like peptide 1 (GLP-1) had effect on insulin secretion only in RYGB patients, both symptomatic and asymptomatic.…”
Section: Hypoglycemia and Dumping Syndromementioning
confidence: 99%
“…Eighteen studies assessed stomach motility. Eleven studies were conducted in Europe (Spain [ n = 2] [ 14 , 15 ], Italy [ n = 3] [ 16 18 ], Greece [ n = 3] [ 19 21 ], Czech Republic [ n = 1] [ 22 ], Germany [ n = 1] [ 23 ], and the Netherlands [ n = 1] [ 24 ]), whereas one study was performed in the USA [ 25 ], two studies in India [ 26 , 27 ], one study in New Zealand [ 28 ], one in Egypt [ 29 ], one in Chile [ 30 ], and one in Israel [ 31 ]. Twelve studies were prospective studies, four studies were prospective randomized controlled studies [ 14 , 17 , 22 , 27 ], and two were retrospective studies [ 18 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Existe acuerdo entre la mayoría de los autores que confirman que el vaciamiento gástrico es acelerado después de GVT. Melissas y nosotros mismos informamos un vaciamiento gástrico más rápido para sólidos y líquidos 12,[39][40][41][42][43][44]. Por el contrario, Bernstine 45 no confirmó los mismos hallazgos para una comida semisólida sugiriendo que el vaciamiento gástrico no se ve afectado después de la GVT con preservación del antro.…”
Section: Vaciamiento Gástricounclassified